THE DEMOCRATIZATION OF TREASURY: A FRAMEWORK FOR SCALABLE FINANCIAL GOVERNANCE IN MID-SIZED ORGANIZATIONS - Borges, Leandro (Revista Gênero e Interdisciplinaridade, 2026)
Corporate treasury practices, traditionally associated with large corporations with vast resources, are often perceived as inaccessible to medium-sized organizations. This article challenges this perception, arguing that the absence of a structured treasury function is a critical vulnerability that can be addressed through the “democratization” of its essential practices. Through a systematic literature review based on the PRISMA protocol, we investigate the principles that allow the adaptation of treasury models to less complex contexts. The analysis focuses on three conceptual pillars: scalability of operating models, proportionality of financial governance, and rationalization of critical processes. From the critical synthesis of the literature, which reveals a gap between robust corporate models and the pragmatic needs of medium-sized companies, we propose the Scalable Treasury Framework (STF). This framework is not a simplified version of corporate treasury, but a conceptual model that guides the implementation of a treasury function based on principles of modularity and focus on the elements with the greatest impact on risk control and decision-making. The article concludes by discussing the implementation challenges and outlining a research agenda for the empirical validation of the STF.